Effect of anticipatory guilt, argument quality and source credibility on attitude towards voluntary simplicity value dimensions among Malaysian youth - Chatterjee, Rajat Subhra (2022)
Engagement in Voluntary Simplicity behaviour can be strongly attributed to contributing towards environmental protection through consumption reduction. The attitudinal inclination towards adopting VS values has mostly been observed on the degree of awareness and current behaviour of individuals. In the present study, the main scope of this study is to observe the relative effect of causal intervention of anticipatory guilt, argument quality, and source credibility manipulation through message design on attitude towards voluntary simplicity value adoption. The study was designed as a quasiexperimental observation of the manipulated variables on attitude towards adoption of the VS value dimensions. The chosen target population was Malaysian youth from different ethnic background. The sample was drawn from the Malaysian youth population using the multi-stage cluster sampling method. The message design and manipulation were duly verified by a panel of experts. The result of ANCOVA analysis shows significant direct effects on each of the VS values namely material simplicity, social responsibility, self-sufficiency, and spiritual growth. Subsequently by undertaking the mean comparison of the interaction effects between the manipulated variables, the study also found strong interaction effects of anticipatory guilt and argument quality at high and low intervention levels towards youth attitude. The result clearly establishes the effect of persuasive message design towards changing attitude through both central and peripheral route and provides a new orientation towards propagating VS value dimensions and its respective adoption within the youth community. The outcome implies that attitude towards voluntary simplicity values can be manipulated through message communication. It further signifies that consumption attitude of Malaysian youth can be further improved through competent and effective message design.